THE PORTRAYAL OF JAVANESE WOMEN FORTITUDE IN ENTROK BY OKKY MADASARI : (A MORAL MESSAGES ANALYSIS) - Nabila, Yugistia Azma; Thamrin, Husni; Supian, Supian (English Education and Applied Linguistics Journal (EEAL Journal), 2022)
This study aims to show how the Javanese women's characteristics depict moral messages in a literary work. The research is entitled "The Portrayal of Javanese Women Fortitude in Entrok by Okky Madasari (A Moral Messages Analysis)". The main source of this research is the novel by Okky Madasari titled Entrok and the translated version titled The Years of the Voiceless as an English reference. The result of data analysis showed that the Javanese women have some types of strength and firmness stance that can be moral messages to society, especially for women. In order to find out the moral messages of the main character as Javanese women in the novel, the writer will use the qualitative research method to finish. Furthermore, the writer will also analyse the data from the novel using descriptive analysis. The result is that the amount of data is much different between Sumarni and Rahayu where Sumarni dominates the message of moral values in the novel, hence the main character who can be chosen as a Javanese woman who portrays fortitude in this novel mostly tends to be Sumarni. From the rigid theory about Javanese women’s characteristics, this novel tends to show that women are not simply can be identified as easy to regulated creatures by men. Sumarni and Rahayu depict that women have the power to determine their path in life.